Notes on a Few Rare, Endemic and Red Listed Species from High Range (Mannavanshola) near Munnar, Idukki District, Kerala State - Udayan, P. S. (Indian Forester, 2006)
During botanical survey conducted in Mannavanshola, near Munnar Idukki District of Kerala State, India, as a part of establishing an Ayurvedic Medicinal Plants Field Gene Bank at Arya Vaidyasala, Kottakkal, round 25 rare, endemic and red listed species were collected. Information about these is presented here in detail with enumeration, distribution, phenology, habitat and critical notes.